The Way of Improvement Leads Home : Philip Vickers Fithian and the Rural Enlightenment in Early America - Fea, John (Early American studies., 2008)
The Way of Improvement Leads Home traces the short but fascinating life of Philip Vickers Fithian. Born to Presbyterian grain-growers in rural New Jersey, he was never quite satisfied with the agricultural life he seemed destined to inherit. Fithian longed for something more- to improve himself in a revolutionary world that was making upward mobility possible. Fithian is best known for the diary that he wrote in 1773-74 while working as a tutor at Nomini Hall, the Virginia plantation of Robert Carter, and his role as a Revolutionary War chaplain. From the villages of New Jersey, Fithian was able to participate indirectly in the eighteenth-century republic of letters- a transatlantic intellectual community. Participation required a commitment to self-improvement that demanded a belief in the Enlightenment values of human potential and social progress. He constantly struggled to reconcile this quest for a cosmopolitan life with his love of home. It was the people, the religious culture, and the very landscape of his "native sod" that continued to hold Fithian's affections.